Morphological ontogeny of Carinogalumna erciyesi sp. nov. (Acari, Oribatida, Galumnidae) from Turkey, with comments on Carinogalumna Engelbrecht - Seniczak, Stanisław; Seniczak, Anna (Zootaxa, 2023)
The morphological ontogeny of Carinogalumna erciyesi sp. nov. from Turkey is described and illustrated. The adult of this species is most similar to that of C. montana Engelbrecht, 1973 but differs from it mainly by the shape of the bothridial seta and porose areas Aa and A2. The larva of C. erciyesi has 12 pairs of gastronotal setae, including alveolar h3, nymphs have 15 pairs; most setae are of medium size and barbed, except for short p2 and p3, smooth in protonymph; setae p2 and p3 are inserted on unsclerotized integument. In all juveniles the bothridial seta is clavate with long, narrow, barbed head. The gastronotal shield is well-developed with setae of d-, l-series and h1 in the larva, and of d-, l-, h-series and p1 in the nymphs. Setae of c-series of juveniles are inserted on microsclerites, and genital opening is placed on a large sclerite. In all juveniles a humeral organ is present, with porose area above it.